2012
DOI: 10.1007/s00432-012-1305-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma human neutrophil proteins-1, -2, and -3 levels in patients with bladder cancer

Abstract: The preoperative plasma levels of HNPs 1-3 paralleled the progression and pathological stages of the malignancies. This study suggests that HNPs 1-3 promote tumor invasion and are potential indicators of disease progression in patients with bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…[43] found that patients with bladder cancer have increased levels of 3 neutrophil proteins, human neutrophil protein-1, -2, and -3 (HNP 1–3). All three HNPs are subtypes of α-defensins, proteins that aid in the recruitment of leukocytes and might contribute to metastasis.…”
Section: Neutrophilsmentioning
confidence: 99%
See 2 more Smart Citations
“…[43] found that patients with bladder cancer have increased levels of 3 neutrophil proteins, human neutrophil protein-1, -2, and -3 (HNP 1–3). All three HNPs are subtypes of α-defensins, proteins that aid in the recruitment of leukocytes and might contribute to metastasis.…”
Section: Neutrophilsmentioning
confidence: 99%
“…This may be accomplished as a result of HNPs promoting cytokine release, stimulating monocytes, and inhibiting the fibrinolytic system. The HNPs found in cancer cells are primarily derived from tumor invading neutrophils and eosinophils [43,44]. Gunes and colleagues [43] found that the levels of all three HNPs were overexpressed in the plasma of the tested bladder cancer patient population, potentially due to neutrophil damage (n=30).…”
Section: Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced defensin levels have been observed in the congenital disease “specific granule deficiency,” acquired defensin deficiencies occasionally in patients with chronic myelogenous leukemia, associated with an increased risk for infections caused by common bacteria . Stimulated expression of α‐defensins is obviously not exclusively associated with microbial infections, but also, for example, with active autoimmune diseases, acute coronary artery disease, or progredient cancer . In our study, some HD patients had a history of autoimmune disease (2 patients with lupus erythematosus), confirmed coronary heart disease (19 patients), or cancer (condition after cancer of the kidney [5], prostate [4], skin [2], breast [1], colon [2]), but at the time of the study all were on stable conditions.…”
Section: Discussionmentioning
confidence: 64%
“…17 Stimulated expression of α-defensins is obviously not exclusively associated with microbial infections, but also, for example, with active autoimmune diseases, 18 acute coronary artery disease, 19 or progredient cancer. 20 In our study, some HD patients had a history of autoimmune disease (2 patients with lupus erythematosus), confirmed coronary heart disease (19 patients), or cancer (condition after cancer of the kidney [5], prostate [4], skin [2], breast [1], colon [2]), but at the time of the study all were on stable conditions. We observed for none of these diagnoses in periods free of infection a significantly increased α-defensin expression compared with the other patients (data not shown).…”
Section: Figurementioning
confidence: 77%